MISTERI BURUNG BERACUN (Pitohui dicrous) DARI PEGUNUNGAN ARFAK, MANOKWARI. - Amon A. Rumbino; Amson D. Flassy; Hans S. Ihalauw (FMIPA Universitas Papua, 2007)
An observation was carried out to reveal the mystery of the poison bird Pitohui dichrous from the Arfak Mountains. According to the Arfak tribe, the poison came from plants (Amorphalus galbra and Alocasia flabellifera) and not from the beetle such as in PNG. Therefore, a furthur study was needed to reveal the poison of Pitohui dicrous from the Arfak mountains